Analysis of elasto-hydrodynamic lubrication of journal bearing based on different numerical methods. Issue 5 (10th August 2015) - Meng, Fanming; Chen, Yuanpei
Abstract : Purpose: – The purpose of this study is to analyze and compare the tribological performances of journal bearings at different conditions through four numerical methods, which are based on the Boussinesq elastic half-space hypothesis or finite element theory. Design/methodology/approach: – An elasto-hydrodynamic lubrication (EHL) model of journal bearings is established, with the oil film pressure obtained by the finite difference method, and the deformation of bearing calculated by four different numerical methods, i.e. the direct finite element method (DFEM), influence coefficient method (ICM), fast-Fourier transform method (FFTM) and direct Boussinesq method (DBM). The tribological performances of the journal bearings obtained with the four methods along with the computation efficiency of the methods are discussed. Findings: – Under different operation conditions, the tribological performances with the finite element method-based methods (DFEM and ICM) agree with each other, and so do those with the Boussinesq-based methods (FFTM and DBM). Compared with the former two methods, the latter two overestimate the friction coefficient, film thickness and bearing deformation, but underestimate the film pressure, load-carrying capacity and friction force. The above discrepancies depend on the lubricant viscosity, the eccentricity ratio and rotational speed of the shaft and the length–diameter ratio of the bearing. Among the four methods, the FFTM has the best computation efficiency, followed by the DBM and the FEM-based methods. Originality/value: – This study conducts detailed discussions of the numerical methods used in the EHL calculation of journal bearings and gives a helpful reference to analyses and designs of journal bearings.